Faktor- Faktor yang Mempengaruhi Pelaksanaan Rumoh Gizi Gampong (RGG) dalam Penurunan Stunting - Norisa, Nanda; Julianti, Rina; Basri, Fitra Ermila; Dewita, Dewita; Usrina, Nora; Fitrianda, Yunita (Universitas Malahayati, 2025)
ABSTRACT The presence of Rumoh Gizi Gampong (RGG) is the spearhead for providing basic health services for the community. Primarily to raise awareness among the public to make efforts so that Acehnese children avoid stunting. RGG is a form of community empowerment at the village/gampong level in efforts to prevent stunting. The RGG activities include a combination of specific and sensitive programs for preventing and handling stunting in Aceh. To find out the factors that influence the implementation of Rumoh Gizi Gampong (RGG) in reducing stunting in the Lampahan Community Health Center Work Area, Timang Gajah District, Bener Meriah Regency. The design of this research is in the form of analytical observational with a cross sectional approach. The subjects in this study were 201 mothers of stunted toddlers who had received PMT for 90 days. This research was carried out for 2 months from May-June 2024. The research location was carried out in the working area of the Lampahan Community Health Center, Timang Gajah District, Bener Meriah Regency. Data collection uses a questionnaire. Data were analyzed using the chi-square test with a p value ≥ 0.05. There is a significant relationship between maternal knowledge and the implementation of RGG (0.002), there is a significant relationship between the role of midwives and the implementation of RGG (0.002), there is a significant relationship between the role of cadres and the implementation of RGG (0.003) and there is a significant relationship between the role of community leaders and implementation RGG (0.000). There is a relationship between mother's knowledge, the role of midwives, the role of cadres, the role of community leaders and the implementation of RGG. Keywords: Knowledge, Population Density, Pulmonary Tuberculosis, Case Control ABSTRAK Kehadiran Rumoh Gizi Gampong (RGG) menjadi ujung tombak untuk memberikan layanan kesehatan dasar bagi masyarakat. Utamanya untuk menyadarkan masyarakat supaya melakukan upaya-upaya agar anak-anak Aceh terhindar dari stunting. RGG merupkan bentuk pemberdayaan masyarakat ditingkat Desa/Gampong dalam upaya pencegahan stunting. Adapun kegiatan RGG mencakup kombinasi program- program spesifik dan sensitive untuk pencegahan dan penanganan stunting di Aceh. Untuk mengetahui Faktor-Faktor yang Mempengaruhi Pelaksanaan Rumoh Gizi Gampong (RGG) dalam Penurunan stunting di Wilayah Kerja Puskesmas Lampahan Kecamatan Timang Gajah Kabupaten Bener Meriah. Desain penelitian ini dalam bentuk observasional analitik dengan pendekatan cross sectional. Subjek dalam penelitian ini adalah 201 ibu yang mempunyai balita stunting yang pernah mendapatkan PMT selama 90 hari. Penelitian ini telah dilaksanakan selama 2 bulan dari Mei-Juni 2024. Lokasi penelitian dilaksanakan di wilayah kerja Puskesmas Lampahan Kecamatan Timang Gajah Kabupaten Bener Meriah. Pengumpulan data menggunakan kuesioner. Data dianalisis menggunakan uji chi-square dengan nilai p ≥ 0.05. Ada hubungan secara signifikan antara pengetahuan ibu dengan palaksanaan RGG (0.002), ada hubungan secara signifikan antara peran bidan dengan pelaksanaan RGG (0.002), ada hubungan secara signifikan peran kader dengan pelaksanaan RGG (0.003) dan ada hubungan secara signifikan peran tokoh masyarakat dengan pelaksanaan RGG (0.000). Ada hubungan pengetahuan ibu, peran bidan, peran kader, peran tokoh masyarakat dengan pelaksanaan RGG. Kata Kunci: Faktor Pengetahuan, Peran Bidan, Peran Kader, Peran Tokoh Masyarakat, Pelaksanaan RGG